Spatial-Temporal Distribution of the Burrowing Shrimp Callichirus major (Say, 1818) (Decapoda, Callichiridae) in Preserved Populations of Southeastern Brazil - Laurino, Ivan Rodrigo Abrão [UNESP]; Buchmann, Francisco Sekiguchi [UNESP]; Hernáez, Patricio (Springer Nature, 2020)
The understanding of the processes that regulates the distribution of the resident macroinfauna on sandy beaches is an urgent need at the current global change scenario. Here, we examine whether the spatial-temporal distribution of the burrowing shrimp Callichirus major (Callichiridae) is affected by the climatic and tidal regimes in two sandy beaches of Brazil (José de Menino and Itaguaré), where is totally prohibited the capture of this species. To this end, we counted shrimp burrows across transects plotted perpendicular to the water line. We found that C. major had a non-random pattern of distribution with dense aggregations of burrows near to the low-tide line. Burrow density and distribution of C. major did not differ across the annual cycle, not following the remarkably environmental seasonality of the southeastern region of Brazil. However, both population parameters were adversely affected when C. major was subject to a high tidal variability. Also, the probability of C. major builds a gallery in intertidal habitats is greater on beaches with very fine sand and low variability of tide amplitude than on beaches with coarser sediments and greater tidal dynamics. Our results point to survival of C. major is not seriously compromised by temperature and precipitation variations, but rather by eventual changes in the tidal regime and sediments. Considering the current scenario of climate change, we argue in favor of C. major may be a good biological model to assess the potential impact of tidal flooding connected to the sea level rise and erosion on coastal habitats.
Keywords: Ghost shrimp; Global changes; Intertidal zonation; Sandy beaches; Seasonality; Tidal amplitude